Heteroleptic copper(II) complexes of prenylated flavonoid osajin behave as selective and effective antiproliferative and anti-inflammatory agents - Vančo, Ján; Trávníček, Zdeněk; Hošek, Jan; Dvořák, Zdeněk (Journal of inorganic biochemistry, 2022)
Heteroleptic copper(II) complexes, containing prenylated flavonoid osajin isolated from the fruits of Maclura pomifera Schneid., were prepared and thoroughly characterized, including single crystal X-ray analysis. Some of the following complexes of the general composition [Cu(L)(bpy)]NO3 (1), [Cu(L)(dimebpy)]NO3·2MeOH (2) [Cu(L)(phen)]NO3·H2O (3), [Cu(L)(bphen)]NO3 (4) and [Cu(L)(dppz)]NO3 (5), where HL stands for 3-(4-hydroxyphenyl)-5-hydroxy-8,8-dimethyl-6-(3-methylbut-2-ene-1-yl)-4H,8H-benzo[1,2-b:3,4-b']dipyran-4-one (osajin), bpy = 2,2'-bipyridine, dimebpy = 4,4'-dimethyl-2,2'-bipyridine, phen = 1,10-phenanthroline, bphen = 4,7-diphenyl-1,10-phenanthroline and dppz = dipyrido[3,2-a:2',3'-c]phenazine, were also monitored for their solution stability and interactions with cysteine and glutathione by mass spectrometry. The in vitro cytotoxicity of the complexes was evaluated against a panel of eight human cancer cell lines: (MCF-7, HOS, A549, PC-3, A2780, A2780R, Caco-2, and THP-1). The results revealed high antiproliferative activity of the complexes with the best IC50 values of 0.5-3.4 μM for complexes (4) and (5), containing the bulkier N,N'-donor ligands (bphen, and dppz, respectively). The complexes also revealed a relatively low toxicity towards human hepatocytes (IC50 values are higher than 100 μM in some cases), and thus proved to be highly selective towards the cancer cells. On the other hand, the complexes showed a strong in vitro nuclease effect using the model pUC-19 plasmid. In the model of lipopolysaccharide-stimulated (LPS) THP-1 monocytes, the complexes revealed ability to lower the activity of nuclear factor kappa-B/activator protein 1 (NF-κB /AP-1) system and decrease the secretion of tumor necrosis factor alpha (TNF-α). Thus, the complexes have been identified as strong antiproliferative and anti-inflammatory compounds.
Keywords: Caco-2 Cells; MCF-7 Cells; Hepatocytes; A549 Cells; buňky PC-3; Inflammation; Coordination Complexes; Copper; antiflogistika; Cell viability; Caco-2 buňky; komplexní sloučeniny; X-ray structure; měď; Cell Proliferation; MFC-7 buňky; In vitro cytotoxicity; hepatocyty; isoflavony; Isoflavones; Anti-Inflammatory Agents; Humans; Copper(II) complexes; PC-3 Cells; Osajin; proliferace buněk; THP-1 buňky; buňky A549; THP-1 Cells; lidé